Polyphenol Iongel Patches with Antimicrobial, Antioxidant and Anti-Inflammatory Properties - Luque, Gisela Carina (2023)
There is an actual need for developing materials for wound healing applications with anti-inflammatory, antioxidant, or antibacterial properties in order to improve the healing performance. In this work, we report the preparation and characterization of soft and bioactive iongel materials for patches, based on polymeric poly(vinyl alcohol) (PVA) and four ionic liquids containing the cholinium cation and different phenolic acid anions, namely cholinium salicylate ([Ch][Sal]), cholinium gallate ([Ch][Ga]), cholinium vanillate ([Ch][Van]), and cholinium caffeate ([Ch][Caff]). Within the iongels, the phenolic motif in the ionic liquids plays a dual role, acting as a PVA crosslinker and a bioactive compound. The obtained iongels are flexible, elastic, ionic conducting, and thermoreversible materials. Moreover, the iongels demonstrated high biocompatibility, non-hemolytic activity, and non-agglutination in mice blood, which are key-sought material specifications in wound healing applications. All the iongels have shown antibacterial properties, being PVA-[Ch][Sal], the one with higher inhibition halo for Escherichia Coli. The iongels also revealed high values of antioxidant activity due to the presence of the polyphenol, with the PVA-[Ch][Van] iongel having the highest activity. Finally, the iongels show a decrease in NO production in LPS-stimulated macrophages, with the PVA-[Ch][Sal] iongel displaying the best anti-inflammatory activity (>63% at 200 µg/mL).